Efficient preparation of TMSCCl2Br and its use in dichlorocyclopropanation of electron deficient alkenes - Lee, Darren S.; Durán-Peña, Maria Jesus; Burroughs, Laurence; Woodward, Simon (Wiley-VCH Verlag, 2016)
The reaction of excess TMSCl and LiCCl2Br at low temperature is a technically simple high yield route to TMSCCl2Br. The latter is a stable source of the dichlorobromomethide carbanion, which undergoes 1,4-addition with cyclic nitroalkenes and (E)-fumarates leading to dichlorocyclopropanes after bromide explusion. For nitrostyrenes the reaction arrests at the 1,4-addition product. Low temperature NMR studies and DFT calculations suggest the formation of an ‘ate’ species [(nitronate)SiFMe3]- which, upon boil off of TMSF at 10 - 20 °C, yields the cyclopropane. DFT calculations also support the experimental differences between fluoride and acetate as promotors.